The impact of institutions on the development of corporate governance in Saudi Arabia - Bukhari, Mazin Sirajuddin (2014)
Recent studies highlight the importance of improving corporate governance practices in order to reduce the impact of financial crises on the economy. However, doing so requires consideration of exactly what forms corporate governance, particularly in a national context. Such consideration necessitates some focus on institutions, an area which has been largely neglected by previous research. As such, this research primarily focuses on understanding a range of institutions in a non-Western, emerging society. Attention will be paid to the influence of such institutions on the emergence and development of corporate governance regimes from an institutional theory perspective, as perceived by significant social actors. Data were collected from semi-structured interviews with corporate governance managers in Saudi Arabia. Findings suggest that the emergence of corporate governance regimes in a non-Western, emerging society (Saudi Arabia) is influenced by family, kinship, bureaucratic state, and religion institutions. Family and kinship institutions appear to negatively impact on the emergence and development of corporate governance in this non-Western, emerging society in terms of issues surrounding control, abuse, and conflict of interest. The bureaucratic state and religion appear to positively influence the development of corporate governance in the Saudi Arabian non-Western, emerging society in terms of issues centred on implementation, compliance, and supporting roles. This research provides a new understanding of the impact of, and role played by, institutions in the formation of corporate governance in a non-Western, emerging society which is an under-researched context. Implications, such as how to reduce negative institutional impacts and take advantage of more positive ones, are discussed. Finally, suggestions for further research are offered. Such research might focus on exploring the impact of institutions from extended standpoints of institutional theory, for example institutional logics and institutional work perspectives.